Implications of financial exclusions for microentreprises under development in Ilorin, Nigeria - Adewale, Abideen Adeyemi; Daud, Mustafa; Abdulkadir, Rihanat Idowu (IIUM Press, 2015)
This study was based on the overriding concern for appraising the appropriateness of access to finance and microenterprises development as the latest poverty alleviation strategy in Nigeria. It is quite likely that poverty in Nigeria may be linked to the financial exclusion of the poor. This frustrates their entrepreneurial activities in the sense of being able to exit from the poverty trap they are immersed in. Relevant information was collected from some poor micro-entrepreneurs in the Ilorin metropolis of Kwara State, Nigeria. This was done using the survey questionnaire. Data so obtained were subjected to data analysis using the Structural Equation Modeling (SEM). The results indicated that both involuntary and voluntary financial exclusion barriers exist. They significantly account for the financial exclusion of the micro-entrepreneurs under sample. Such financial exclusion was found to significantly explain the underdevelopment of microenterprises in Nigeria. Recommendations contingent on research findings and best global practices were offered.